Quality Planning for Frontier, Remote, and Disadvantaged (3T) Schools in Supporting the Strengthening of Literacy and Numeracy - Norhanah; Jasiah (Yayasan Payungi Smart Madani, 2025)
School quality planning in the Frontier, Outermost, and Disadvantaged (3T) regions plays a strategic role in supporting the strengthening of student literacy and numeracy amidst limited access, infrastructure, and human resources. This article aims to analyze and describe the quality planning of 3T schools in supporting the strengthening of literacy and numeracy through a literature review. The research method used is a qualitative approach with a descriptive-analytical library research type, utilizing various relevant literature sources such as books, scientific journals, and educational policy documents. The results of the study indicate that 3T school quality planning needs to be prepared systematically and contextually through the formulation of the school's vision, mission, and objectives, analysis of student and environmental needs, literacy and numeracy program planning, strengthening teacher competencies, and ongoing monitoring and evaluation mechanisms. Stakeholder involvement and utilization of local potential are key factors in addressing the gap in education quality in 3T regions. With targeted and sustainable quality planning, 3T schools have the potential to improve the quality of literacy and numeracy learning while reducing disparities in education quality between regions.